Mindfulness Meditation Changed Interregional Connectivity in Subcortical and Default Mode Networks in Internet Gaming Disorder - Ma, Xuefeng; Wei, Meiting; Ni, Haosen; Li, Shuang; Wang, Huabin; Liu, Chang; Song, Xiaolan; Dong, Guang-Heng (Mindfulness, 2024)
Objectives Although internet gaming disorder (IGD) has become a serious mental health issue throughout the world, current treatment strategies face significant challenges. Mindfulness meditation (MM) is both versatile and widely accepted and has been proposed as an approach for treating IGD. However, its effects on IGD and the potential neural mechanisms underlying MM remain unknown. Methods Sixty-two participants with IGD were included, with 31 assigned to the MM group and 31 to the progressive muscle relaxation (PMR) group, all of them completed the entire experimental procedure, including the pre-test, eight MM training sessions (or progressive muscle relaxation), and the post-test. Two hundred and ten cortical and 36 subcortical subregions were arranged into eight brain networks according to Yeo’s functional template. The brain network features (intra- and inter-modular segregations) were compared between the different groups and tests. Results MM was found to reduce both addiction severity and gaming cravings in IGD subjects. In terms of brain networks, MM increased modular segregation in the subcortical network (SCN), especially between frontoparietal network (FPN)-SCN, and dorsal attentional network (DAN)-SCN, while also increasing connections in nodes in default mode networks (DMN), especially between FPN-DMN and DAN-DMN. Significant correlations between behavioral and network features were found. PMR also generated similar effects but inferior to MM. Conclusions MM was found decreased gaming craving and addiction severity in treating IGD. The process was associated with enhanced top-down control functions. The findings have implications for both clinicians and researchers. Preregistration The protocol of the trial has been pre-registered at the Chinese clinical trial registry ( www.chictr.org.cn ; ChiCTR2300075869).